Evaluación sobre el conocimiento del uso de el cigarrillo electrónico y su incidencia en las enfermedades respiratorias en personas de 15 a 25 años Parroquia Barreiro-Babahoyo, octubre 2019-marzo 2020. - Moyano Troya, Joyce Deyanira (2020)
The purpose of this research is to evaluate the knowledge of the use of electronic cigarettes and their incidence in respiratory diseases in people aged 15 to 25. For the analysis of this study an inductive method was required by the nature of the research, from this a quantitative approach was made, to know the problems caused by the use of electronic cigarettes in young people and adolescents from 15 to 25 years, to demonstrate whether they have proper knowledge about this device. In addition, the analysis of results was carried out through statistical tools that will allow to demonstrate that the present work is valid. The field research identified aspects and factors that influence the use of this device by young people and adolescents; showing that the majority of young people and adolescents do not know anything about electronic cigarettes, they only do it for fun and popularity, therefore the Ministry of Public Health should train young people and adolescents and family members or representatives, about the electronic cigarette to control and avoid risks of contracting respiratory diseases by using this device.